Safety of borehole water as an alternative drinking water source - Nathaniel Owusu Boadi; Selina Ama Saah; Frimpomah Baa-Poku; Ebenezer Adom Mensah; Malik Addo (Scientific African, 2020)
The quality of drinking water is necessary for good health. In this study, twenty borehole drinking water samples were collected from homes and communities and assessed for their quality. The results indicated that 95 % of the samples had pH values below the World Health Organization's (WHO) drinking water guidelines of 6.5–8.5. The pH values obtained ranged from 4.33–7.03. The other physicochemical parameters fell within the WHO's set limits for drinking water. The concentrations of the cations (Ca2+, Mg2+, Na+ and K+) fell within the WHO drinking water limits. About 55% of the samples had nitrate concentrations above the WHO threshold, with concentrations ranging from 0.04 to 107.57 mg/L. The SO42−, PO43− and Cl− concentrations for the samples were within the WHO set limits. The water quality index calculated for the water samples was 54.25, indicating that the water samples were not safe to drink. Also, 85% of the water samples were contaminated with both total and faecal coliforms, making them unsuitable for drinking.